Pengembangan Multimedia Pembelajaran Interaktif Pada Materi Perubahan Wujud Benda Siswa Kelas V SDN Kraton - Aulivia Devi Andini; Muhammad Basori; Wahyudi Wahyudi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The research objective was to determine the validity, practicality and effectiveness of PowerPoint-based interactive learning multimedia products using the Research and Development method using the ADDIE model. The subjects of this study were teachers and fifth grade students at SDN Kraton. The instruments used include observation, interviews, questionnaires, evaluation questions and documentation. The results of this study are as follows: (1) the validity of multimedia is seen from the validation results of material experts and media experts obtaining a percentage of 85%, so that this media can be declared very valid and feasible to use, (2) the practicality of multimedia is based on the results of a questionnaire the response of class V teachers at SDN Kraton obtained a percentage of 90%. While the results of the response of class V students at SDN Kraton obtained a score of 174 with a percentage of 96%, (3) the effectiveness of multimedia is very effectively used for the learning process because the post-test results of class V students obtain a percentage of Mastery Learning Classical (KBK) of 85%.